2019
DOI: 10.1038/s41398-019-0662-8
|View full text |Cite|
|
Sign up to set email alerts
|

Running exercise protects oligodendrocytes in the medial prefrontal cortex in chronic unpredictable stress rat model

Abstract: Previous postmortem and animal studies have shown decreases in the prefrontal cortex (PFC) volume and the number of glial cells in the PFC of depression. Running exercise has been shown to alleviate depressive symptoms. However, the effects of running exercise on the medial prefrontal cortex (mPFC) volume and oligodendrocytes in the mPFC of depressed patients and animals have not been investigated. To address these issues, adult male rats were subjected to chronic unpredictable stress (CUS) for 5 weeks, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…In the CUS/running group, the animals ran on a six-lane motorized treadmill for 20 min per day, 5 days per week for 6 weeks. The running speed was gradually increased from 10 to 20 m/min during the first week and then maintained at 20 m/min for the next 5 weeks 42 44 . The control group and the CUS/standard group were housed under conditions are not subjected to running exercise.…”
Section: Methodsmentioning
confidence: 99%
“…In the CUS/running group, the animals ran on a six-lane motorized treadmill for 20 min per day, 5 days per week for 6 weeks. The running speed was gradually increased from 10 to 20 m/min during the first week and then maintained at 20 m/min for the next 5 weeks 42 44 . The control group and the CUS/standard group were housed under conditions are not subjected to running exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Graham et al (2019) found that exercise increased the oligodendrocytes in the white matter of a mouse model of obesity. Recently, our team found that running exercise significantly increased the number of CNPase-positive oligodendrocytes in the medial prefrontal cortex of the chronic unpredictable stress rat model (Luo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that an increase in size or number of macro-glia cells would have a significant effect on the DW-MRI signal, thus contributing to the positive association here observed between physical lifestyle scores and WM extra-neurite fraction (by construction 1 minus intra-neurite density (NODDI f-intra), and specifically, the hindered space outside the neurites prescribed through anisotropic diffusion). Crucially, there exists key histological evidence from animal studies in support of an increase in astrocyte proliferation and in glial fibrillary acidic protein (GFAP) levels (Li et al 2005;Uda et al 2006) and in oligodendrocytes number (Luo et al 2019) in several areas of the rat brain. Together with this previous literature, the findings here reported may suggest a positive relationship between physically active lifestyle and macro-glia cell density across multiple WM tracts, perhaps reflecting a role in providing enhanced metabolic support for neurons.…”
Section: Discussionmentioning
confidence: 99%